A single nucleotide polymorphism in the Epstein-Barr virus genome is strongly associated with a high risk of nasopharyngeal carcinoma. Issue 3 (December 2015) - Feng, Fu-Tuo; Cui, Qian; Liu, Wen-Sheng; Guo, Yun-Miao; Feng, Qi-Sheng; Chen, Li-Zhen; Xu, Miao; Luo, Bing; Li, Da-Jiang; Hu, Li-Fu; Middeldorp, Jaap; Ramayanti, Octavia; et al.
Abstract Background Epstein-Barr virus (EBV) commonly infects the general population and has been associated with nasopharyngeal carcinoma (NPC), which has a high incidence in certain regions. This study aimed to address how EBV variations contribute to the risk of NPC. Methods Using logistic regression analysis and based on the sequence variations at EBV-encodedRPMS1, a multi-stage association study was conducted to identify EBV variations associated with NPC risk. A protein degradation assay was performed to characterize the functional relevance of theRPMS1 variations. Results Based on EBV-encodedRPMS1 variations, a single nucleotide polymorphism (SNP) in the EBV genome (locus 155391: G>A, named G155391A) was associated with NPC in 157 cases and 319 healthy controls from an NPC endemic region in South China [P < 0.001, odds ratio (OR) = 4.47, 95% confidence interval (CI) 2.71–7.37]. The results were further validated in three independent cohorts from the NPC endemic region (P < 0.001, OR = 5.20, 95% CI 3.18–8.50 in 168 cases vs. 241 controls, andP < 0.001, OR = 5.27, 95% CI 4.06–6.85 in 726 cases vs. 880 controls) and a non-endemic region (P < 0.001, OR = 7.52, 95% CI 3.69–15.32 in 58 cases vs. 612 controls). The combined analysis in 1109 cases and 2052 controls revealed that the SNP G155391A was strongly associated with NPC (P combined < 0.001, OR = 5.27, 95% CI 4.31–6.44). Moreover, the frequency of the SNP G155391A was associated with NPC incidence but was not associated with the incidences of other EBV-related malignancies. Furthermore, the protein degradation assay showed that this SNP decreased the degradation of the oncogenic RPMS1 protein. Conclusions Our study identified an EBV variation specifically and significantly associated with a high risk of NPC. These findings provide insights into the pathogenesis of NPC and strategies for prevention.